An amino-terminal tetrapeptide specifies cotranslational degradation of beta-tubulin but not alpha-tubulin mRNAs. - Bachurski, C J (1994)
The steady-state level of alpha- and beta-tubulin synthesis is autoregulated by a posttranscriptional mechanism that selectively alters alpha- and beta-tubulin mRNA levels in response to changes in the unassembled tubulin subunit concentration. For beta-tubulin mRNAs, previous efforts have shown that this is the result of a selective mRNA degradation mechanism which involves cotranslational recognition of the nascent amino-terminal beta-tubulin tetrapeptide as it emerges from the ribosome. Site-directed mutagenesis is now used to determine that the minimal sequence requirement for conferring the full range of beta-tubulin autoregulation is the amino-terminal tetrapeptide MR(E/D)I. Although tubulin-dependent changes in alpha-tubulin mRNA levels are shown to result from changes in cytoplasmic mRNA stability, transfection of wild-type and mutated alpha-tubulin genes reveals that alpha- and beta-tubulin mRNA degradation is not mediated through a common pathway. Not only does the amino-terminal alpha-tubulin tetrapeptide MREC fail to confer regulated mRNA degradation, neither wild-type alpha-tubulin transgenes nor an alpha-tubulin gene mutated to encode an amino-terminal MREI yields mRNAs that are autoregulated. Further, although slowing ribosome transit accelerates the autoregulated degradation of endogenous alpha- and beta-tubulin mRNAs, degradation of alpha-tubulin transgene mRNAs is not enhanced, and in one case, the mRNA is actually stabilized. We conclude that, despite similarities, alpha- and beta-tubulin mRNA destabilization pathways utilize divergent determinants to link RNA instability to tubulin subunit concentrations.